INDUSTRIAL WORK PRACTICES AND SKILLS TO GROW ENTREPRENEURSHIP ATTITUDES IN THE FOOD SERVICE SECTOR FOR STUDENTS OF SMK NEGERI I TONDANO - Jenny Christien Tambahani (Ismart Edu: Jurnal Pendidikan Teknologi Informasi, 2022)
Entrepreneurship is one of the determinants of the economic progress of a nation. The problem that arises is there is any influence of Industrial Work Practices on entrepreneurship attitudes and the influence of skills on entrepreneurship attitudes. Data was obtained from distributing questionnaires to 28 students of SMK Negeri 1 Tondano, which was obtained using simple saturation, then analyzed using quantitative data analysis. Quantitative analysis includes validity and reliability testing, classical assumption test, coefficient of determination test and multiple analysis, F significance test (F statistic test), individual parameter significance test (t-test). While the data processing using SPSS 19.00 for windows. From the results of research data processing obtained from simple linear regression = 6.382 + 0.408 X1 + 0.222 X2 + e. Simultaneous calculation results obtained partial test results for t count (2.835) > t table (2.059), the significance of the Prakerin variable on the related variable, namely the entrepreneurial attitude of 0.009 or less than the alpha value of 0.05. Industrial Work Practices variables have a significant effect on students' entrepreneurial attitudes or H1 is accepted and H2 is rejected. While the regression coefficient of the skill variable is 0.239 or greater than the alpha value of 0.05. So it can be said that the value of t arithmetic t table and significance 0.239 > 0.05 means that the skill variable has no effect and is not significant on students' entrepreneurial attitudes or H1 is rejected and H0 is accepted